(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Disorders of growth and development in children are one of the conditions that are of concern to the government at this time. Based on preliminary observations in Sukaluyu Village, Pangalengan District, and Bandung Regency, there are several Children with Special Needs (ABK) who are not well identified, including in terms of their growth and development. This is the rationale for carrying out counseling activities to identify growth and development disorders in Children with Special Needs (ABK). This activity was held on Monday, December 5, 2022. The service method used was surveys, counseling and questions and answers about growth and development disorders. Based on the description and results of the discussion of this community service activity, it can be concluded that counseling on the identification of developmental disorders in children, especially children with special needs, is one of the efforts that can be made in providing understanding to parents so that they have the potential to minimize the occurrence of growth and development disorders. The response of the participants to this counseling activity was very good, it can be seen from their enthusiasm and liveliness during the question and answer session, moreover there were participants who wanted similar activities in their institutions.